Elevation affects the ecological stoichiometry of Qinghai spruce in the Qilian Mountains of northwest China - Qin, Huijun; Jiao, Liang; Zhou, Yi; Wu, Jingjing; Che, Xichen (Frontiers in Plant Science, 2022)
Environmental heterogeneity in temperature, moisture, and soil fertility caused by elevation gradients can affect the trade-offs in the survival strategies of tree species. There is uncertainty about the allocation of resources to different tissues of trees in response to the elevation gradient with respect to carbon (C), nitrogen (N), and phosphorus (P). Here, the C, N, and P content of leaves, branches, trunks, and thick and fine roots of Picea crassifolia (Qinghai spruce) and their stoichiometric changes across three different elevations were investigated in the Qilian Mountains. We found that N:P of Qinghai spruce was <14 in all tissues at most elevations, indicating that Qinghai spruce was more susceptible to N limitation. Meanwhile, the N content and N:P of Qinghai spruce each were significantly negatively correlated with temperature (p < 0.05), and its P content was lower at high elevation. The contribution of soil–climate interactions on the elevation gradient to each tissue type was 34.02% (leaves), 16.84% (branches), 67.78% (trunks), 34.74% (thick roots), and 49.84% (fine roots), indicating that interacting climate and soil factors on the elevation gradient predominately drove the C, N, and P content and stoichiometry variation in each tissue type of Qinghai spruce trees. The results of this study clarify that the elevation gradient regulates the elemental content and resource allocation in Qinghai spruce, providing basic data and an important timely reference for future forest management in the regions where coniferous trees grows. These findings also help improve our understanding of elevational patterns of forest ecosystem stoichiometry in arid and semiarid regions.